Test template and test method for curing shrinkage of photocuring composition
By designing a multi-pit group test template, the shrinkage rate of the photocuring composition is calculated using the depth and width changes in the pit, the problems of measurement deviation and complex operations in the prior art are solved, and more efficient and accurate photocuring is achieved. The composition curing shrinkage test.
Patent Information
- Application Number
- CN202411298127.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art has deviations and complex operations in the volume shrinkage rate during testing the photocuring process, and requires precise equipment, making it difficult to measure the curing shrinkage properties of the photocuring composition in a convenient and accurate manner.
A test template including multiple pit groups arranged in different depths and widths was designed, and prepared by substrate etching. The shrinkage rate of the photocured composition is calculated using ΔH and ΔL in the pit to simplify the operation process and improve the test accuracy.
A simpler and more accurate curing shrinkage test of photocuring compositions is achieved, reducing deviations and test errors caused by time changes, improving testing efficiency and accuracy, and reducing dependence on complex equipment.
Smart Images

Figure CN119246509A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of applied material testing, and in particular to a testing template and a testing method for curing shrinkage of a photocurable composition. Background Art
[0002] As a common method of material curing processing, photocuring technology is widely used in scientific research and industrial production. However, during the photocuring process, the material will shrink in volume, and the resulting shrinkage stress will form a weak point in the material application process. This phenomenon will not only cause warping and deformation, but also weaken adhesion and reduce mechanical properties.
[0003] At present, there are two ways to test the volume shrinkage rate during the photocuring process, one is the volume shrinkage rate, and the other is the linear shrinkage rate. The traditional method is to calculate the curing shrinkage rate by testing the density difference before and after curing based on the change in volume before and after curing. This may cause the shrinkage rate difference caused by sufficient surface curing and insufficient internal curing. In addition, there will be a wetting problem with the water surface during the density method test, because the actual change in the curing shrinkage rate is small, and problems with surface wetting (such as fine bubbles) will also cause abnormal curing shrinkage. The linear shrinkage rate is the ratio of the length difference before and after curing between the center line of the resin before curing and the two end faces to the length before and after curing. Studies have shown that axial shrinkage is greater than the linear shrinkage of the material. Therefore, if only one of them is measured, a large deviation may occur. In the prior art, CN114179319A invented a volume of the plunger displacement before and after photocuring in an injection molding process, and finally calculated the curing shrinkage rate by continuously compensating the barrel. The whole process requires continuous illumination and provides more photocurable compositions. CN109752315A invented a light-curing shrinkage device for dentistry, which requires displacement sensors on both sides of the sample slot to calculate the curing shrinkage. There are also inventions such as CN115491157A that use a vernier caliper to measure the dimensional changes before and after curing to calculate the volume shrinkage during the light-curing process. In addition, there are documents that design methods such as the bonding disc method, the uniaxial shrinkage measurement method, the digital image correlation method, and the fiber Bragg grating method, all of which require relatively sophisticated equipment and instruments.
[0004] In order to more conveniently and accurately test the volume change of a photocurable composition after sufficient radiation treatment, it is urgently necessary to design a test template for the volume shrinkage rate during the photocuring process. After irradiation, the photocurable composition will react to the template, resulting in possible volume shrinkage. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a test template and a test method for the curing shrinkage of a photocurable composition.
[0006] In the first aspect, the present invention provides a test template for the curing shrinkage rate of a photocurable composition, wherein the test template includes a substrate; and a group of pits distributed on the substrate; wherein the group of pits is composed of a plurality of pits, the width and depth of each pit are arranged in order, and the depth and / or width of each pit are different. The test template designed by the present invention with a plurality of different pits is simple and efficient, and can perform multiple tests on the same sample at one time, reducing the deviation caused by the change of the photocurable composition over time; the designed test template can compare and analyze the results, and has good test accuracy for the curing shrinkage of the photocurable composition. The present invention can measure the photocuring shrinkage in a simpler and more accurate way, overcomes the inaccurate measurement, complex operation and equipment requirements in the prior art solutions, and has a high application prospect.
[0007] Preferably, the test template has at least one pit group arranged in an i×j matrix, wherein i and j are each selected from an integer greater than 1; preferably, i and j are each independently selected from an integer from 4 to 10.
[0008] Preferably, in the pit group, the pits in the same horizontal row have the same length and width, and the depth of the pits increases from left to right; the pits in the same vertical column have the same length and depth, and the width of the pits increases from top to bottom.
[0009] Preferably, the width of the pits in the pit group is 2-55 μm, preferably 5-50 μm; the depth of the pits in the pit group is 2-110 μm, preferably 5-100 μm.
[0010] Further preferably, the pits in the pit group are arranged in a 4×4 matrix.
[0011] Preferably, the widths of the pits in the pit group are 5±2 μm, 10±2 μm, 20±2 μm and 30±2 μm from top to bottom, and the depths are 5±2 μm, 10±2 μm, 20±2 μm and 30±2 μm from left to right.
[0012] Preferably, the pit is a linear pit; preferably, the linear length of the linear pit is greater than 1 mm.
[0013] In a second aspect, the present invention also provides a method for preparing the above-mentioned test template, including etching a substrate to obtain a pit group; preferably, including placing a photosensitive dry film on the substrate, exposing, developing and etching the substrate, and adjusting the etching times of each pit in the pit group to obtain pits with different widths and / or depths.
[0014] Preferably, the substrate contains a copper layer with a thickness of 35 um or more; the substrate is preferably a copper clad laminate.
[0015] In a third aspect, the present invention further provides a method for testing the curing shrinkage of a photocurable composition, using the above-mentioned test template or the test template obtained by the above-mentioned preparation method.
[0016] Preferably, the testing method comprises: filling a plurality of pits of a test template with a photocurable composition, and then performing photocuring, obtaining the depth and width of the pit after photocuring of the photocurable composition, calculating ΔH and ΔL in the pit according to the following formula, calculating the average value of ΔH and the average value of ΔL of some or all of the pits, adding the average value of ΔH to the average value of ΔL to obtain the shrinkage rate of the photocurable composition.
[0017]
[0018] Wherein, H1 is the pit depth, H2 is the pit depth after the photocurable composition is photocured, L1 is the pit width, and L2 is the width of the photocurable composition after photocuring.
[0019] The test template provided by the present invention can not only perform multiple tests on the same sample, but also compare and analyze the test results in the horizontal and vertical directions, so as to more accurately evaluate the curing shrinkage of the photocurable composition. The linear design of the pits in the template can more completely reflect the shrinkage of the same pit during the photocuring process, reduce the test error, and ensure the accuracy of the test. In the specific test process, the present invention calculates the average values of ΔH and ΔL of some or all pits according to the characteristics of the pits through a specific shrinkage test formula ΔH+ΔL, preferably using the diagonal line of the groove group as the dividing line, and measuring the ΔH average value of the upper right part of the groove (the depth of the groove is greater than the width) and the ΔL average value of the lower left part (the depth of the groove is less than the width), and calculates the shrinkage of the whole board. This method provides higher test accuracy by comparing and analyzing the test results of different areas and optimizing the calculation. It can better reflect the shrinkage during the photocuring process, reduce test errors, and further improve test accuracy.
[0020] Preferably, in the pit group, if the depth of the pit is greater than the width of the pit, the average value of ΔH corresponding to the pit is calculated; if the depth of the pit is less than the width of the pit, the average value of ΔL corresponding to the pit is calculated; the shrinkage rate of the photocurable composition is obtained by the average value of ΔH + the average value of ΔL.
[0021] Further preferably, the diagonal line in the pit group is used as the dividing line, the depth of the pit in the upper right part of the dividing line is greater than the width of the pit, and the average value of ΔH corresponding to the pit is calculated; the depth of the pit in the lower left part is less than the width of the pit, and the average value of ΔL corresponding to the pit is calculated; the shrinkage rate of the photocurable composition is obtained by the average value of ΔH + the average value of ΔL.
[0022] The test template and test method for testing the curing shrinkage of a photocurable composition provided by the present invention simplify the operation process, improve the test efficiency, and can also reduce the deviation caused by the time change of the photocurable composition, providing higher test accuracy. The test method of the present invention can more accurately evaluate the curing shrinkage of the photocurable composition, further reduce the test error, and improve the accuracy of the test. The present invention is easy to operate, accurate in measurement, does not require complex equipment, and has a high application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the present invention or the prior art, a brief introduction is given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0024] Figure 1 It is a schematic structural diagram of a test template for the curing shrinkage of a photocurable composition provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] An embodiment of the present invention provides a test template for the curing shrinkage of a photocurable composition, wherein the test template includes a substrate; and a pit group distributed on the substrate; wherein the pit group is composed of a plurality of pits, the width and depth of each pit are arranged in order, and the depth and / or width of each pit are different. The test template with a plurality of different pits designed in the embodiment of the present invention is simple and efficient, and can perform multiple tests on the same sample at one time, reducing the deviation caused by the change of the photocurable composition over time; the designed test template can compare and analyze the results, and has good test accuracy for the curing shrinkage of the photocurable composition. The present invention can measure photocuring shrinkage in a simpler and more accurate way, overcomes the inaccurate measurement, complex operation and equipment requirements in the prior art solutions, and has a high application prospect.
[0027] In a preferred embodiment, the test template has at least one pit group arranged in an i×j matrix, wherein i and j are each selected from an integer greater than 1; preferably, i and j are each independently selected from an integer from 4 to 10. When the test template for the curing shrinkage rate of the photocurable composition provided by the present invention is provided with multiple pit groups on the same test template, multiple samples can be tested simultaneously by attaching different samples, thereby determining the shrinkage rates of different samples. This design reduces the errors caused by multiple operations and improves the efficiency and accuracy of the test.
[0028] According to an embodiment of the present invention, the width and depth of the test template can be set in a reasonable arrangement, and schemes of different widths and depths derived on the basis of the test template of the present invention are all within the protection scope of the present invention.
[0029] As a preferred embodiment, in the pit group, the pits in the same horizontal row have the same length and width, and the depth of the pits increases from left to right; the pits in the same vertical column have the same length and depth, and the width of the pits increases from top to bottom. The pits are arranged in a manner of equal width in the horizontal direction and equal thickness in the vertical direction, and the width of each pit gradually increases from top to bottom, and the depth gradually deepens from left to right. The rules involved in the pits on the test template can test the shrinkage rate of the same sample multiple times at one time, reduce system errors, and can also compare and analyze the test results in the horizontal and vertical directions, which is conducive to improving the test accuracy of the curing shrinkage of the photocurable composition.
[0030] As a preferred embodiment, the width of the pits in the pit group is 2-55 μm, preferably 5-50 μm; the depth of the pits in the pit group is 2-110 μm, preferably 5-100 μm.
[0031] In a further preferred embodiment, the pits in the pit group are arranged in a 4×4 matrix. One pit group of the test template can achieve up to 16 sample filling and measurement on the same plane, and by comparing the changes in different pits, the shrinkage of the photocurable composition can be analyzed, thereby providing more accurate data.
[0032] The design of the test template in the present invention follows the principles of convenience and efficiency, allowing multiple shrinkage tests to be performed on a single sample at one time, and reducing test errors through comparative analysis in the horizontal and vertical directions, thereby more accurately evaluating the curing shrinkage of the photocurable composition. This design simplifies the operating process and improves test efficiency and accuracy. Through this setting, multiple samples can be tested simultaneously on the same test template, effectively reducing errors caused by multiple operations.
[0033] In a preferred embodiment, the width of the pits in the pit group is 5±2μm, 10±2μm, 20±2μm and 30±2μm from top to bottom, and the depth is 5±2μm, 10±2μm, 20±2μm and 30±2μm from left to right. The test template provided by the present invention optimizes the arrangement of the pits in the pit group and adopts a gradual design of width and depth. Specifically, in the preferred design of the present invention, the width of the pits in the pit group increases or decreases from top to bottom, preferably increases, respectively, and is 5±2μm, 10±2μm, 20±2μm and 30±2μm, while the depth gradually deepens or becomes shallower, preferably deepens, from left to right, respectively, and is 5±2μm, 10±2μm, 20±2μm and 30±2μm. Such lateral depth gradient changes and longitudinal width gradient changes can not only ensure multiple tests on a single sample in one operation, but also, through optimized design, more stable test data can be obtained, system errors can be reduced, and the accuracy of the test results can be greatly improved. Furthermore, the depth of the pit in the upper right part of the diagonal area of the pit is greater than the width, and the measured ΔH data can more effectively reflect the shrinkage rate in the depth direction; the width of the pit in the lower left part is greater than the depth, and the measured ΔL data can better reflect the shrinkage rate in the width direction. The arrangement of the pits, the width and depth settings, and the optimized measurement method used in the present invention make the test results more accurate, effectively reduce errors, and improve test efficiency.
[0034] According to an embodiment of the present invention, the test template has the following Figure 1 The structure shown: m1~m4 correspond to lateral rows with widths of 5μm, 10μm, 20μm, and 30μm; n1~n4 correspond to vertical columns with depths of 5μm, 10μm, 20μm, and 30μm; m and n form a matrix; in the figure, the blue part represents the filled photocurable composition.
[0035] As a preferred embodiment, the pit is a linear pit; preferably, the linear length of the linear pit is more than 1 mm, preferably 1-10 mm, such as 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 8 mm, etc. The linearity of the pit can more completely reflect the shrinkage of the same pit during the photocuring process, thereby reducing errors.
[0036] The method for preparing the test template provided in an embodiment of the present invention includes etching a substrate to obtain a pit group; preferably, it includes placing a photosensitive dry film on the substrate, exposing, developing and etching the substrate, and adjusting the etching times of each pit in the pit group to obtain pits with different widths and / or depths.
[0037] The substrate provided in the embodiment of the present invention contains a copper layer with a thickness of 35 um or more; the substrate in the preferred embodiment of the present invention is a copper clad laminate. The photosensitive dry film used can be a common high-resolution adhesive product on the market.
[0038] According to the embodiment of the present invention, the exposure, development and etching are conventional dry film processing methods in the art. The present invention does not limit the specific exposure, development and etching process, as long as the linear pits of different widths and depths in the present invention can be obtained. When etching the template, the present invention takes the right as the bottom and etches in sequence to obtain the pits of different depths; the pits are linear pits; the linear length of the linear pits is at least 1 mm; thus, a test template with different widths and different depths on the same plane is obtained.
[0039] The method for testing the curing shrinkage of a photocurable composition provided in an embodiment of the present invention adopts the above-mentioned test template or the test template obtained by the above-mentioned preparation method.
[0040] According to an embodiment of the present invention, any number of pits can be filled during the photocurable composition filling process of the test template, for example, 2 or more pits can be filled in the same row; preferably, 16 pits arranged in a 4×4 matrix can be filled for the same sample.
[0041] In the embodiment of the present invention, the test template can test the same sample 16 times at a time, and the test results are analyzed by data analysis based on the light curing effects at different depths, and the average value is taken to obtain the curing shrinkage rate of the light curing composition.
[0042] According to an embodiment of the present invention, the test method for the curing shrinkage of the photocurable composition is applicable to photosensitive dry films. The microscope may be a scanning electron microscope or a metallographic microscope.
[0043] In some embodiments of the present invention, a plurality of pits are set on the test template, and the photocurable composition is filled into these pits, and then the photocuring treatment is performed to obtain the depth and width of the pit after photocuring. According to the formula, the ΔH and ΔL in the pit are calculated, and the average values of the ΔH and ΔL of some or all pits are calculated, and finally the two average values are added to obtain the shrinkage rate of the photocurable composition. This method can test the shrinkage rate of multiple samples at one time, thereby reducing the error caused by multiple operations and improving the test efficiency. The test method provided by the present invention has higher test accuracy, the width and depth of the pits are arranged in order, and different width and depth designs can effectively analyze the shrinkage of the photocurable composition under different conditions, provide more accurate data support, and calculate the average values of the ΔH and ΔL of the pits above and below the diagonal, and add them, which can effectively compensate and reduce the measurement error and provide more reliable test results. Compared with the complex equipment and operation in the prior art, this test method is simple to operate, and the present invention can complete the filling and testing of 16 pits at the same time, improve the test efficiency, and is suitable for application scenarios such as photosensitive dry film and PCB printed circuit board. The method of the present invention significantly improves test efficiency and reduces operation complexity and errors while maintaining high test accuracy, and is an important innovation in the test of curing shrinkage of photocurable compositions.
[0044] As a preferred embodiment, the testing method includes: filling a plurality of pits of a test template with a photocurable composition, and then performing photocuring, obtaining the depth and width of the pit after the photocurable composition is photocured, calculating ΔH and ΔL in the pit according to the following formula, calculating the average value of ΔH and the average value of ΔL of some or all of the pits, adding the average value of ΔH to the average value of ΔL to obtain the shrinkage rate of the photocurable composition.
[0045]
[0046] Wherein, H1 is the pit depth, H2 is the pit depth after the photocurable composition is photocured, L1 is the pit width, and L2 is the width of the photocurable composition after photocuring.
[0047] The test template provided by the embodiment of the present invention can not only perform multiple tests on the same sample, but also compare and analyze the test results in the horizontal and vertical directions, so as to more accurately evaluate the curing shrinkage of the photocurable composition. The linear design of the pits in the template can more completely reflect the shrinkage of the same pit during the photocuring process, reduce the test error, and ensure the accuracy of the test. In the specific test process, the present invention calculates the average values of ΔH and ΔL of some or all pits according to the characteristics of the pits through a specific shrinkage test formula ΔH+ΔL, preferably using the diagonal line of the groove group as the dividing line, and measuring the ΔH average value of the upper right part of the groove (the depth of the groove is greater than the width) and the ΔL average value of the lower left part (the depth of the groove is less than the width), and calculates the shrinkage of the whole board. This method provides higher test accuracy by comparing and analyzing the test results of different areas and optimizing the calculation. It can better reflect the shrinkage during the photocuring process, reduce test errors, and further improve test accuracy.
[0048] According to some embodiments provided by the present invention, the photocurable composition is composed of oligomers, monomers and initiators, etc.; a dye is preferably added to the photocurable composition; when no drying treatment is required, the configured photocurable composition is coated on a test template to fill the pits in the test template, and then the excess photocurable composition on the surface of the test template is scraped off; when a solvent is added to the photocurable composition, it is required to be dried in advance, the dried photocurable coating is laminated on the test template, the pits in the test template are filled, and then the excess coating sample on the surface of the test template is scraped off; after the sample is prepared on the test template, the test template is placed in an ultraviolet light curing device, filled with nitrogen and isolated from oxygen for light curing; then a microscope is used to observe the height change of the photocurable composition in the pits, and the curing shrinkage rate is calculated therefrom.
[0049] As a preferred embodiment, in the pit group, if the depth of the pit is greater than the width of the pit, the average value of ΔH corresponding to the pit is calculated; if the depth of the pit is less than the width of the pit, the average value of ΔL corresponding to the pit is calculated; the shrinkage rate of the photocurable composition is obtained by the average value of ΔH + the average value of ΔL.
[0050] According to an embodiment of the present invention, if the depth of a pit is equal to the width of the pit, the average value of ΔH or the average value of ΔL is not calculated; in addition, if the depth of a pit is equal to the width of the pit, the average value of ΔH may be calculated together with the pits whose depth is greater than the width, or the average value of ΔL may be calculated together with the pits whose depth is less than the width, or (ΔH+ΔL) / 2 may be calculated, etc., all of which are considered to be within the protection scope of the present invention.
[0051] In a further preferred embodiment, the diagonal line in the pit group is used as the dividing line, the depth of the pit in the upper right part of the dividing line is greater than the width of the pit, and the average value of ΔH corresponding to the pit is calculated; the depth of the pit in the lower left part is less than the width of the pit, and the average value of ΔL corresponding to the pit is calculated; the shrinkage rate of the photocurable composition is obtained by the average value of ΔH + the average value of ΔL. In the embodiment of the present invention, the shrinkage rate of the photocurable composition corresponding to the pit is calculated by using ΔH + ΔL, and the width change below the diagonal line of the test template matrix is compensated. Compared with the existing curing shrinkage determination method, such as calculating the curing shrinkage rate by the difference in thickness change before and after curing or observing whether the filling is complete to judge, the test method of the present invention can greatly improve the test accuracy of the curing shrinkage of the photocurable composition.
[0052] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A test template for curing shrinkage of a photocurable composition, characterized in that: The test template includes a substrate; and a pit group distributed on the substrate; wherein the pit group consists of a plurality of pits, the width and depth of each pit are arranged in sequence and the depth and / or width of each pit are different.
2. The test template according to claim 1, characterized in that: The test template has at least one pit group arranged in an i×j matrix, wherein i and j are each selected from an integer greater than 1; preferably, i and j are each independently selected from an integer from 4 to 10.
3. The test template according to claim 2, characterized in that: In the pit group, the pits in the same transverse row have the same length and width, and the depth of the pits increases from left to right; the pits in the same longitudinal column have the same length and depth, and the width of the pits increases from top to bottom.
4. The test template according to any one of claims 1 to 3, characterized in that: The width of the pits in the pit group is 2-55 μm, preferably 5-50 μm; the depth of the pits in the pit group is 2-110 μm, preferably 5-100 μm; And / or, the pits in the pit group are arranged in a 4×4 matrix; preferably, the widths of the pits in the pit group are 5±2 μm, 10±2 μm, 20±2 μm and 30±2 μm from top to bottom, and the depths are 5±2 μm, 10±2 μm, 20±2 μm and 30±2 μm from left to right; And / or, the pit is a linear pit; preferably, the linear length of the linear pit is greater than 1 mm.
5. The method for preparing the test template according to any one of claims 1 to 4, characterized in that: It includes etching the substrate to obtain a pit group; preferably, it includes placing a photosensitive dry film on the substrate, exposing, developing and etching the substrate, and adjusting the etching times of each pit in the pit group to obtain pits with different widths and / or depths.
6. The preparation method according to claim 5, characterized in that: The substrate contains a copper layer with a thickness of 35um or more; the substrate is preferably a copper clad laminate.
7. A method for testing the curing shrinkage of a photocurable composition, characterized in that: A test template obtained by using the test template described in any one of claims 1 to 4 or the preparation method described in claim 5 or 6.
8. The testing method according to claim 7, characterized in that: include: Filling a plurality of pits of a test template with a photocurable composition, and then photocuring the composition, obtaining the depth and width of the pit after photocuring, calculating ΔH and ΔL in the pit according to the following formula, calculating the average value of ΔH and the average value of ΔL of some or all pits, and adding the average value of ΔH to the average value of ΔL to obtain the shrinkage rate of the photocurable composition; Wherein, H1 is the pit depth, H2 is the pit depth after the photocurable composition is photocured, L1 is the pit width, and L2 is the width of the photocurable composition after photocuring.
9. The testing method according to claim 8, characterized in that: In the pit group, if the depth of the pit is greater than the width of the pit, the average value of ΔH corresponding to the pit is calculated; if the depth of the pit is less than the width of the pit, the average value of ΔL corresponding to the pit is calculated; the shrinkage rate of the photocurable composition is obtained by the average value of ΔH + the average value of ΔL.
10. The testing method according to claim 9, characterized in that: Taking the diagonal line in the pit group as the dividing line, the depth of the pit in the upper right part of the dividing line is greater than the width of the pit, and the average value of ΔH corresponding to the pit is calculated; the depth of the pit in the lower left part is less than the width of the pit, and the average value of ΔL corresponding to the pit is calculated; the shrinkage rate of the photocurable composition is obtained by the average value of ΔH + the average value of ΔL.
